PENINGKATAN KETAHANAN PANGAN MASA PANDEMI COVID-19 DI NGROPOH KRANGGAN TEMANGGUNG - Victory Cindy Maylana; Ari Prasetyo; Syamsul Hadi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
In early 2020 the whole world was shaken by the Covid-19 pandemic, which caused panic everywhere. The impact of the Covid-19 pandemic has disrupted various aspects of life such as health, social, economic, etc. One of the main problems is food security, which is currently becoming a very active topic of conversation. Based on these problems, community service through UNS KKN activities is carried out with work programs to improve food security in the form of cultivation and viticulture, increase the role of the Abimanyu reservoir, and additional programs to support food security in Ngropoh Village, Kranggan District, Temanggung Regency. The results of community service activities show that the community has experienced an increase in fulfilling their daily food needs and can live and carry out activities more healthily